2015
DOI: 10.3389/fmicb.2015.00533
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Eimeria mitis expressing chicken interleukin 2 stimulated higher cellular immune response in chickens compared with the wild-type parasites

Abstract: Chicken coccidiosis, caused by Eimeria sp., occurs in almost all poultry farms and causes huge economic losses in the poultry industry. Although this disease could be controlled by vaccination, the reduced feed conservation ratio limits the widespread application of anticoccidial vaccines in broilers because some intermediate and/or low immunogenic Eimeria sp. only elicit partial protection. It is of importance to enhance the immunogenicity of these Eimeria sp. by adjuvants for more effective prevention of coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…However, a significant local immunity in the MLN was detected. Previous work in our laboratory (8) on transgenic chicken Eimeria demonstrated that enhanced cellular immunity was detected in PBMC of chickens immunized with transgenic parasites expressing chicken IL-2. However, the systemic immune response, at least in our rabbits, was low after primary infection of EmagWT or EmagER , consistent with a previous study on the dynamics of T-lymphocytes in rabbits immunized with E. intestinalis (28).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, a significant local immunity in the MLN was detected. Previous work in our laboratory (8) on transgenic chicken Eimeria demonstrated that enhanced cellular immunity was detected in PBMC of chickens immunized with transgenic parasites expressing chicken IL-2. However, the systemic immune response, at least in our rabbits, was low after primary infection of EmagWT or EmagER , consistent with a previous study on the dynamics of T-lymphocytes in rabbits immunized with E. intestinalis (28).…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies demonstrated that the exogenous protein expressed by transgenic parasites stimulate specific immune responses in the host. One study (8) showed that immunization with a transgenic E. mitis line expressing chicken IL-2 stimulated an enhanced cellular immune response against it. In addition, a transgenic line of E. tenella expressing Toxoplasma gondii SAG1 protein (TgSAG1) elicits protective immunity against T. gondii in chicken and mice (9).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic manipulation to improve the safety and efficacy of anticoccidiosis vaccines have been extensively studied in recent years (28)(29)(30)(31). Enhancing the immunogenicity of live oocyst formulations via expressing molecular adjuvants is one of the most active and promising attempts (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic manipulation to improve the safety and efficacy of anticoccidiosis vaccines have been extensively studied in recent years (28)(29)(30)(31). Enhancing the immunogenicity of live oocyst formulations via expressing molecular adjuvants is one of the most active and promising attempts (29,30). Li and colleagues used interleukin 2 (IL-2), a critical cytokine for T cell activation and proliferation, to enhance the immunogenicity of E. mitis and demonstrated that the protection provided by transgenic E. mitis expressing IL-2 is nearly 3-fold better than that provided by the wild type in experimental settings (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation